2021
DOI: 10.1088/1757-899x/1107/1/012120
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics (CFD) Analysis of Buoyancy Flow in A Differentially Heated Square Cavity

Abstract: The present study analyzes conjugate heat transfer in a differentially heated square cavity. The left wall of the cavity is cooled, and the right wall is heated while the horizontal walls are adiabatic. Normalized continuity, momentum and energy transport equations were solved with the aid of COMSOL Multiphysics 5.4 software. The effects of Rayleigh number in the range of 102 ⩽ RA ⩽ 106 and Prandtl number in the range of 0.71 ⩽ PR ⩽ 100 on streamlines, isotherms, and the overall heat transfer in the cavity are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Buoyancy initiated flow in a trapezoidal enclosure whose vertical sides were under isothermal heating whereas the inclined walls were cooled was analyzed numerically by Al-Makhyoul [9]; they recognized that the average Nusselt number rises as the Rayleigh number is raised but decreases as baffle length and the number of baffles increase. Also, Olayemi et al [10] also considered the influence of Rayleigh number in a buoyancy induced flow and their submission is in congruence with the view of [9]. Bejan [11] studied free convective flow in a porous vertical enclosure and opined that Rayleigh number dictated the accuracy of the Weber Method and that the heat transferred is enhanced by increasing Rayleigh number.…”
Section: Introductionmentioning
confidence: 77%
“…Buoyancy initiated flow in a trapezoidal enclosure whose vertical sides were under isothermal heating whereas the inclined walls were cooled was analyzed numerically by Al-Makhyoul [9]; they recognized that the average Nusselt number rises as the Rayleigh number is raised but decreases as baffle length and the number of baffles increase. Also, Olayemi et al [10] also considered the influence of Rayleigh number in a buoyancy induced flow and their submission is in congruence with the view of [9]. Bejan [11] studied free convective flow in a porous vertical enclosure and opined that Rayleigh number dictated the accuracy of the Weber Method and that the heat transferred is enhanced by increasing Rayleigh number.…”
Section: Introductionmentioning
confidence: 77%
“…It was indicated that internal heat generation promoted heat transfer, while heat absorption discouraged heat transfer enhancement. Olayemi et al 24 reported the effects of Prandtl and Rayleigh numbers in a square domain subjected to different heating modes and driven by buoyancy forces. They reported the relationship between Nusselt and Rayleigh numbers, and that low Prandtl number fluids (like, air and water) are preferred in achieving a very high heat transfer rate than fluids of high Prandtl numbers, which are expensive but result in an insignificant increase in heat transfer enhancement when compared with fluids of low Prandtl number.…”
Section: Introductionmentioning
confidence: 99%
“…However, with double-diffusive natural convection, increasing the Grashof number increases average Nu and the overall heat transfer rate [38]. The implications of Rayleigh number and geometric parameters on natural and mixed convective heat transfer in relevant enclosures were emphasized [39][40][41][42][43][44][45][46][47]. Salari et al [48] conducted a numerical study to determine the influence of turbulent transient models on natural convection in trapezoidal cavities.…”
Section: Introductionmentioning
confidence: 99%